PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BALAI BESAR METEOROLOGI, KLIMATOLOGI, DAN GEOFISIKA WILAYAH II TANGERANG SELATAN - Ningdyah, Melsa Puspita; Andi, Dede (Journal of Research and Publication Innovation, 2024)
This study is to determine whether there is an influence of Organizational Culture and Work Discipline on Employee Performance both partially and simultaneously. This research was conducted using quantitative methods involving 79 employees as samples. With data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study, namely the variables of Organizational Culture, Work Discipline and Employee Performance, obtained a multiple regression equation (Y) = 5.202 + 0.149€ + 0.714X2 + e. The regression coefficient value on the employee performance variable 5.202 concludes that if the Organizational Culture (X1) and Work Discipline (X2) remain (no change) then the consistency value of Performance (Y) is 5.202. concluded that if the Organizational Culture (X1) and Work Discipline (X2) remain (no change) then the consistency value of Performance (Y) is 5,202. The statistical results of the t test there is a positive and significant effect of Organizational Culture on employee performance. based on the table that the tcount is 9.179> ttable 1.995 or significantly 0.000 <0.05 so partially there is a positive and significant effect of Organizational Culture (X1) on employee performance (Y). Based on the table that the tcount is 14.293> ttable 1.995 and significantly 0.000 <0.05, thus partially there is a positive and significant effect of Work Discipline (X2) on employee Performance (Y). And, the results of statistical calculations show the value of f-count 105.927> f-table 3.117 using a significance limit of 0.05. It can be said that the hypothesis which states that simultaneously the variables of Organizational Culture (X1), Work Discipline (X2) have an influence on employee performance (Y).